PENGEMBANGAN MEDIA KARTU KUARTET BERBANTUAN QR-CODE MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN PAKINTELAN 01 SEMARANG - Qurrota Aini, Salsa; Sunarso, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the low learning outcomes of Pancasila Education in class V and the interactive learning media used by teachers is still limited. Thus, this research aims to develop, test the feasibility and test the effectiveness of the Qr-Code assisted Quartet Card media in the Pancasila Education subject with a focus on Indonesian Cultural Diversity in Class V SDN Pakintelan 01. The type of research applied is research and development (R&D) by applying the ADDIE development model whose stages include analysis, design, development, implementation, evaluation. The instruments used in this research were interviews, observation sheets, tests, questionnaires and documentation. For data analysis using the normality test, t test, and n-gain test. This research provides data results in the form of feasibility validation results from media experts reaching 90%, and material experts reaching 89%. The results of the pretest and posttest for the large-scale group showed an N-Gain value of 0.5209 in the medium category and an effectiveness percentage of 52%. Based on these results, it shows that the Quartet Card media assisted by Qr-Code is effective and feasible to be applied in improving student learning outcomes in the Pancasila Education subject for Class V Elementary School.